2015
DOI: 10.3389/fpsyg.2015.01273
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion influences PTSD symptoms in the process of change in trauma-focused cognitive-behavioral therapies: a study of within-person processes

Abstract: Although self-compassion is considered a promising change agent in the treatment of posttraumatic stress disorder (PTSD), no studies of this hypothesis exist. This study examined the within-person relationship of self-compassion components (self-kindness, common humanity, mindfulness, self-judgment, isolation, over-identification) and subsequent PTSD symptoms over the course of therapy.Method: PTSD patients (n = 65) were randomized to either standard prolonged exposure, which includes imaginal exposure (IE) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 28 publications
(45 reference statements)
4
44
0
4
Order By: Relevance
“…This is in line with the emerging support for compassion-oriented interventions [87] and self-compassion as a potent mechanism of change within psychotherapy for PTSD [88]. The current review found evidence that psychotherapy may help contain the toxic effects of shame, creating a buffer between experiences of shame and trauma-related distress [39].…”
Section: Discussionsupporting
confidence: 80%
“…This is in line with the emerging support for compassion-oriented interventions [87] and self-compassion as a potent mechanism of change within psychotherapy for PTSD [88]. The current review found evidence that psychotherapy may help contain the toxic effects of shame, creating a buffer between experiences of shame and trauma-related distress [39].…”
Section: Discussionsupporting
confidence: 80%
“…For instance, after 8 weeks of mindful self‐compassion training (Neff & Germer, ) participants reported a 30% increase in compassionate and a 33% decrease in uncompassionate responding toward the self (Neff, , ). This pattern has been observed for a wide variety of methodologies such as self‐compassion meditation training (Albertson et al, ; Toole & Craighead, ; Wallmark, Safarzadeh, Daukantaitė, & Maddux, ); online psycho‐education (Finlay‐Jones, Kane, & Rees, ; Krieger, Martig, van den Brink, & Berger, ); affect training (Hildebrandt, McCall, & Singer, ); imaginal exposure therapy (Hoffart, Øktedalen, & Langkaas, ); self‐compassion field training (Khorami, Moeini, & Ghamarani, ); compassion‐based Kg‐Free weight reduction training (Pinto‐Gouveia et al, ); compassion‐focused therapy (Beaumont, Irons, Rayner, & Dagnall, ; Kelly & Carter, ); compassionate mind training (Arimitsu, ; Beaumont, Rayner, Durkin, & Bowling, ); and mindful self‐compassion (Finlay‐Jones, Xie, Huang, Ma, & Guo, , Friis et al, , see Footnote 2; Neff, ). Mindfulness‐based interventions also yield a simultaneous increase in compassionate SCS subscale scores and a decrease in uncompassionate SCS subscale scores: for example, mindfulness‐based stress reduction (Birnie, Speca, & Carlson, ; Raab, Sogge, Parker, & Flament, ); mindfulness‐based cognitive therapy (Kuyken et al, , see Footnote 2); and Koru (Greeson, Juberg, Maytan, James, & Rogers, ).…”
Section: Discussionmentioning
confidence: 74%
“…using bipolar constructs: kindness vs self-judgement; mindfulness vs self-absorption/over identification, and common humanity vs isolation. Low scores, indicating low self-compassion, are highly correlated with experiences of paranoia, shame and self-criticism [88]; post traumatic stress disorder [60]; depression [95] and mental health problems in general [15,83,97].…”
Section: Self-compassionmentioning
confidence: 99%